PROPAGANDA TERHADAP UMAT ISLAM JAWA DI ZAMAN JEPANG, 1942-1945 - tendi tendi (Jurnal Tamaddun : Jurnal Sejarah dan Kebudayaan Islam, 2018)
AbstractThe period of Japanese occupation was one of the important phases of Indonesia's independence. This paper aims to find out how propaganda directed to Muslims by the Japanese military government to support and perpetuate their power in the Archipelago. From this study it is known that in its efforts to maintain the power and power of Allied attacks, Japan approached elements of Indonesian society. One of the targets is the Muslims, who are considered Japan as the majority group that can be invited to cooperation. On that basis, Japan then propaganda specifically against Muslims by: 1) Active in Islamic Religious Activities; 2) Make Aprroaches to Islamic Leaders; 3) Alignments in Education Policy; and 4) Establishment of Institutions for Islamic Groups.Keywords: propaganda, Muslims, Japanese period, military government